Use Of The Standard Forecasting Error (SKP) Method To Predict The Costs Of Maintenance Of State Confiscious Goods: Case Study Of A State Storage House For Confiscated Objects In Central Maluku - Chrestiana Aponno; Wa Asrida (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
State confiscated objects are objects seized by investigators,prosecutors or officials because of his position have the authority to confiscate the goods for purposes of evidence in court prosedings.Because the objects of state property confiscated,the competent author shall Mainten the goods gonfiscated,the government also must pay maintenance confiscated good. With the number of confiscated goods that exist in the home country seized goods storage and maintenance costs that donot match the number of seized goods belonging to the state. Research is to be ableto predict the magnitudeof the cost of maintenance of seized goods in the next 5 years by using standart methods of forcasting error.The result obtained SKP trand value curve of 8,26 issmaller than the pad SKPstraight line trand of 26,9 in predicting the maintenance cost of confiscated goods,which is very appropriate method used is trend curve method for predicting the cost of encumbrances from2015 until 2019..